2020
DOI: 10.1186/s13613-020-00663-x
|View full text |Cite
|
Sign up to set email alerts
|

Bedside prediction of intradialytic hemodynamic instability in critically ill patients: the SOCRATE study

Abstract: Background: Despite improvements in intermittent hemodialysis management, intradialytic hemodynamic instability (IHI) remains a common issue that could account for increased mortality and delayed renal recovery. However, predictive factors of IHI remain poorly explored. The objective of this study was to evaluate the relationship between baseline macrohemodynamic, tissue hypoperfusion parameters and IHI occurrence. Methods: Prospective observational study conducted in a 18-bed medical ICU of a tertiary teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Beyond routinely available clinical information, predicting tolerance to fluid removal may require adjunct information including dynamic assessment of preload responsiveness at the bedside [ 41 ] and other sources of information. In a recent study, a combination of cardiovascular SOFA score, capillary refill time and serum lactate achieved moderate performance in predicting hemodynamic instability [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond routinely available clinical information, predicting tolerance to fluid removal may require adjunct information including dynamic assessment of preload responsiveness at the bedside [ 41 ] and other sources of information. In a recent study, a combination of cardiovascular SOFA score, capillary refill time and serum lactate achieved moderate performance in predicting hemodynamic instability [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might again be explained by the different fluid removal rates: in the present study, the fluid removal rate was fixed during the study period, whereas in the study by Klijn et al [55] it was doubled every 15 min. Bigé et al [56] observed that an index CRT > 3 s had a reasonably good predictive value for intradialytic hypotension, but this measure was less reliable in our patients (AUC 0.62 vs 0.71), perhaps because we included fewer patients with a CRT > 3 s at baseline (27% vs 55%, respectively).…”
Section: Discussionmentioning
confidence: 71%
“…Hypoperfusion as de ned in our study was not a known prognostic factor considering patients with CRRT, but it is physiologically plausible that it may impede organ failure recovery. Besides, capillary re ll time has been described as a predictor of poor hemodynamic tolerance during RRT (32) and small variations in volemia can be detected by capillary re ll time variations (33). In our opinion, it promotes strict hemodynamic monitoring during deresuscitation to avoid the side effects related to inadequate forced uid removal.…”
Section: Hemodynamic Tolerance Of the Perfusion-based Deresuscitation...mentioning
confidence: 89%